Praktik Endorsement Sebagai Strategi Pemasaran Perspektif Mazhab al-Syafi'i - Mutmainnah M; Jamil (Universitas Islam Negeri Alauddin Makassar, 2023)
This article aims to find out the implementation of endorsement practices as a marketing strategy, and to understand the perspective of the Syafi'i school on the implementation of endorsement practices as a marketing strategy. The research method that the author does is qualitative research, namely by using library research (Library Research) while the approach used is descriptive and syar'i. Qualitative research is research that is used to investigate, find, describe, and explain the quality or features of social influences that cannot be explained, measured or described through a quantitative approach. the implementation of this endorsement practice is carried out by providing information on an item or product through social media carried out by a public figure. Based on the results of this study indicate that the marketing strategy through endorsement according to Imam Syafi'i can be used as long as it is in accordance with the contract in the sale and purchase and no losses are incurred. In this contemporary era, everything will switch to the world of technology or digital and all possibilities will happen, including strategies in marketing products that will follow the times and will bring creativity in trading electronically. This era has been read by Imam Shafi'i, therefore the Shafi'i school explains that as long as it does not eliminate the rights and obligations of the sale and purchase contract, it is permissible.